The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1477-7517-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic- and gender-specific differences in the prevalence of HIV among patients in opioid maintenance treatment—a case register analysis

Abstract: BackgroundWe have sought to identify ethnic- and gender-specific differences in HIV prevalence among heroin users receiving opioid maintenance treatment in the canton of Zurich, Switzerland.MethodsWe used a generalized linear model (GEE) to analyze data from the anonymized case register for all opioid maintenance treatments in the canton of Zurich. Patients who received either methadone or buprenorphine between 1991 and 2012 (n = 11,422) were evaluated for gender (male vs. female), ethnic background (Swiss vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In addition, Greenfield and colleagues (2007) identified pregnancy, lack of services for pregnant women, fear of losing custody for a new born, or fear of prosecution, coupled with lack of child care outside of treatment, to be gender-specific barriers keeping women from entering treatment for substance use disorders (Ashley, Marsden, & Brady, 2003;Schober & Annis, 1996). Furthermore, women have repeatedly been reported to experience greater social stigma and discrimination than males, when entering treatment programs for substance abuse (Kline, 1996;Liebrenz, Stohler, & Nordt, 2014). Such barriers must be addressed by crime reduction policies and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Greenfield and colleagues (2007) identified pregnancy, lack of services for pregnant women, fear of losing custody for a new born, or fear of prosecution, coupled with lack of child care outside of treatment, to be gender-specific barriers keeping women from entering treatment for substance use disorders (Ashley, Marsden, & Brady, 2003;Schober & Annis, 1996). Furthermore, women have repeatedly been reported to experience greater social stigma and discrimination than males, when entering treatment programs for substance abuse (Kline, 1996;Liebrenz, Stohler, & Nordt, 2014). Such barriers must be addressed by crime reduction policies and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that BZD dependence in this group could have partly been avoided by offering low-threshold access to treatment [ 53 , 54 ]. Although it has been suggested that this reason for initiating BZD use has decreased in importance because of the increased availability of OMT in Switzerland over the last decades [ 55 , 56 ], it might still be a significant factor for patients elsewhere who have less access to maintenance therapy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be related either to additive hERG channel blockade or to increased serum drug concentrations resulting from changes in metabolism . An estimated 10–15% of all heroin users are HIV‐positive , and medication‐assisted opioid treatment programs provide structure including directly administered treatment that increase adherence to anti‐retroviral therapy . Therefore, HIV‐positive opioid addicts on anti‐retroviral therapy may represent an important subgroup of patients at higher risk of cardiac arrhythmia due to QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%